2003
DOI: 10.1074/jbc.m308463200
|View full text |Cite
|
Sign up to set email alerts
|

Different Isoforms of Synapse-associated Protein, SAP97, Are Expressed in the Heart and Have Distinct Effects on the Voltage-gated K+ Channel Kv1.5

Abstract: The SAP97 isoforms differ by alternatively spliced insertion domains that regulate protein localization and oligomerization. We used reverse transcription-PCR to identify SAP97 isoforms of human and rat myocardium. In Chinese hamster ovary cells, cloned protein expression was studied using Western blot, confocal imaging of green fluorescent protein-tagged proteins, and patch clamp technique. The two main cardiac SAP97 isoforms contained both I3 and I1B inserts and differed by the I1A insert. Both isoforms co-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Indeed, Kv1.5 current is not enhanced by the cardiac SAP97 isoform containing the I1A domain, which prevents protein oligomerization (145,199). Oligomerization of SAP97 is regulated by inter-and intramolecular interactions (302), which determines the conformation of SAP97: compact "closed" state (preventing binding of ligands to the SH3 and GUK domains) or "open" state, allowing access to the protein binding sites (456).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Kv1.5 current is not enhanced by the cardiac SAP97 isoform containing the I1A domain, which prevents protein oligomerization (145,199). Oligomerization of SAP97 is regulated by inter-and intramolecular interactions (302), which determines the conformation of SAP97: compact "closed" state (preventing binding of ligands to the SH3 and GUK domains) or "open" state, allowing access to the protein binding sites (456).…”
Section: Figurementioning
confidence: 99%
“…In the heart, two SAP97 isoforms are expressed, both containing the alternatively spliced insertions I3 and I1B, but differing in the presence or absence of I1A (145). SAP97 contains different combinations of alternatively spliced insertions that regulate the subcellular localization of the protein and its capacity to homo-or heterodimerize (247,270).…”
Section: Figurementioning
confidence: 99%
“…9,10 SAP97 regulates the targeting and localization of cardiac potassium channels, such as Kir2.x 11 and K v 1.5 in myocytes. 10 El-Haou et al 12 recently demonstrated that SAP97 interacts with K v 4.2 and K v 4.3 channels via their PDZ-domain binding motif. They showed that suppression of SAP97 expression in rat myocytes decreases the K v 4.x-mediated current, whereas its overexpression increases it.…”
mentioning
confidence: 99%
“…As already shown in other cell types derived from the cardiovascular system, i.e. smooth muscle cells and cardiomyocytes, the larger and the shorter isoforms of Dlg1 differ, in endothelial cells, by an N-terminal insertion of a small proline-rich sequence named I1A that is due to the presence of a site of alternative splicing in the mRNA (data not shown) (35,36). In the larger form, an SH3 binding site is thus present that may bind the SH3 domain of a number of protein tyrosine kinases or of Dlg1 itself in an intra-or an extramolecular way that favors a "closed state" or the homomultimerization of the protein, respectively (37).…”
Section: Discussionmentioning
confidence: 87%